2011
DOI: 10.1128/mcb.00847-10
|View full text |Cite
|
Sign up to set email alerts
|

Med25 Is Required for RNA Polymerase II Recruitment to Specific Promoters, Thus Regulating Xenobiotic and Lipid Metabolism in Human Liver

Abstract: Hepatocyte nuclear factor 4␣ (HNF4␣) controls the expression of many critical metabolic pathways, and the Mediator complex occupies a central role in recruiting RNA polymerase II (Pol II) to these gene promoters. An impaired transcriptional HNF4␣ network in human liver is responsible for many pathological conditions, such as altered drug metabolism, fatty liver, and diabetes. Here, we report that Med25, an associated member of the Mediator complex, is required for the association of HNF4␣ with Mediator, its se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 70 publications
6
59
0
Order By: Relevance
“…Formaldehyde-assisted Isolation of Regulatory Elements (FAIRE)-HepG2 cells cultured in 100-mm dishes were infected with adenovirus expressing LacZ, CAR, or HNF4␣ or were co-infected with CAR plus HNF4␣ with FLAG-MED25 or CAR plus HNF4␣ with shMED25 (11). After 48 h, chromatin was isolated from non-cross-linked and cross-linked (1% formaldehyde for 10 min) cells, sheared to 200 -500-bp fragments in a Diagenode Bioruptor, and subjected to multiple rounds of extraction with an equal volume of phenol/chloroform.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Formaldehyde-assisted Isolation of Regulatory Elements (FAIRE)-HepG2 cells cultured in 100-mm dishes were infected with adenovirus expressing LacZ, CAR, or HNF4␣ or were co-infected with CAR plus HNF4␣ with FLAG-MED25 or CAR plus HNF4␣ with shMED25 (11). After 48 h, chromatin was isolated from non-cross-linked and cross-linked (1% formaldehyde for 10 min) cells, sheared to 200 -500-bp fragments in a Diagenode Bioruptor, and subjected to multiple rounds of extraction with an equal volume of phenol/chloroform.…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism of nuclear receptor-mediated activation involves recruitment of the Mediator complex by HNF4␣, which we found to occur specifically through direct interaction with the variable Mediator subunit MED25 (11). The metazoan Mediator complex is composed of 30 distinct subunits, which are variably associated with transcriptional cofactors such as the glucocorticoid receptor (12), CREB-binding protein (CREBBP) (13), and the preini-tiation complex (PIC) (14) in a cell-and promoter-contextspecific manner.…”
mentioning
confidence: 92%
“…It has been shown that the MED25 counterparts from animals physically associate with multiple cellular transcriptional activators, including the herpes simplex viral activator VP16 (Mittler et al, 2003;Yang et al, 2004), RAR (Lee et al, 2007), hepatocyte nuclear factor4 (Rana et al, 2011), and the chondrogenesis-related transcriptional activator Sox9 (Nakamura et al, 2011). Our data showing that mutation of the Arabidopsis MED25 gene affects the action of MYC2 in regulating the expression of JA-responsive genes prompted us to characterize the physical interaction of the two proteins in vivo.…”
Section: Mapping Of the Domains Involved In The Med25/ Myc2 Interactionmentioning
confidence: 99%
“…One of them is Med25, which is absent in yeast but plays a role in the regulation of xenobiotic metabolism and lipid homeostasis in human liver (Rana et al, 2011). A biochemical screen identified Arabidopsis PFT1 as Med25 (Bäckströ m et al, 2007).…”
Section: Expression Profile Of the Kinase Module And Other Associatedmentioning
confidence: 99%